Checking of Automatically Scaled Ionograms by Infinite Impulse Response Filters - Rejfek, Luboš; Beran, Ladislav; Chmelař, Pavel; Fišer, Ondřej; Zálabský, Tomáš; Řezníček, Michal (IEEE (Institute of Electrical and Electronics Engineers), 2016)
This paper is about using of the infinite impulse response (IIR) filters for the checking of the automatically scaled ionograms. This method is based on the detection of the extreme deviation in the data sequence of the ionospheric parameters (Total Electron Concentration, critical frequency of F2 layer and virtual height of F2 layer). Used types of the IIR filters are low-pass filters (Butterworth, Chebyshev1, Chebyshev2, and Elliptic). Described method using the data from the observatory Pruhonice measured in January 2016 was tested. These data were measured during the geomagnetic storm. Results were very surprising for the virtual height of the layer F2.
Kontrola automaticky vyhodnocených ionogramů pomocí IIR filtrů
Keywords: Ionosphere; Ionogram; Scaling of ionograms; Infinite Impulse Response (IIR) Filter; Spectrum; Ionogram, IIR filtry, spektrum, ionosféra